Genetic diversity, clinical uses, and phytochemical and pharmacological properties of safflower (Carthamus tinctorius L.): an important medicinal plant - Cheng, Hao; Yang, Chenglong; Ge, Pengliang; Liu, Yi; Zafar, Muhammad Mubashar; Hu, Beibei; Zhang, Tong; Luo, Zengchun; Lu, Siyu; Zhou, Qin; Jaleel, Abdul; Ren, Maozhi (Frontiers in Pharmacology, 2024)
Safflower (Carthamus tinctorius L.), a member of the Asteraceae family, is widely used in traditional herbal medicine. This review summarized agronomic conditions, genetic diversity, clinical application, and phytochemicals and pharmacological properties of safflower. The genetic diversity of the plant is rich. Abundant in secondary metabolites like flavonoids, phenols, alkaloids, polysaccharides, fatty acids, polyacetylene, and other bioactive components, the medicinal plant is effective for treating cardiovascular diseases, neurodegenerative diseases, and respiratory diseases. Especially, Hydroxysafflor yellow A (HYSA) has a variety of pharmacological effects. In terms of treatment and prevention of some space sickness in space travel, safflower could be a potential therapeutic agent. Further studies are still required to support the development of safflower in medicine. Our review indicates that safflower is an important medicinal plant and research prospects regarding safflower are very broad and worthy of further investigation.